2002
DOI: 10.1097/01.lab.0000022224.86237.31
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Tubular Epithelial Cell Integrins Respond to High Glucose by Altered Cell-Matrix Interactions and Differentially Regulate Matrixin Expression

Abstract: SUMMARY:Thickening of the tubular basement membrane (TBM) occurs in diabetic nephropathy, but the effects of high glucose on the functional aspects of proximal tubular epithelial cells are not clearly understood. In the present study, we examined the effects of elevated glucose concentrations on (a) integrin expression by human proximal tubular epithelial cells (HK-2) and integrin-mediated interactions with type IV collagen (colIV) and laminin, major components of TBM; (b) the expression of matrixins/matrix me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
15
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 75 publications
4
15
0
4
Order By: Relevance
“…Cells were cultured on several substrates including EHS-derived intact laminin (corresponding to laminin 1), intact collagen IV (composed of (α1)2(α2) chains) or intact human GBM. It was previously reported that these substrates promote cell adhesion, differentiation, or gene expression in cultured podocytes Krishnamurti et al, 1997;Krishnamurti et al, 2001;Kobayashi et al, 2001;Kitsiou et al, 2003) and other epithelial cells of the kidney Karamessinis et al, 2002). We showed that EHS-derived laminin (laminin 1), up-regulated the expression of PC by HGEC.…”
Section: Discussionsupporting
confidence: 54%
“…Cells were cultured on several substrates including EHS-derived intact laminin (corresponding to laminin 1), intact collagen IV (composed of (α1)2(α2) chains) or intact human GBM. It was previously reported that these substrates promote cell adhesion, differentiation, or gene expression in cultured podocytes Krishnamurti et al, 1997;Krishnamurti et al, 2001;Kobayashi et al, 2001;Kitsiou et al, 2003) and other epithelial cells of the kidney Karamessinis et al, 2002). We showed that EHS-derived laminin (laminin 1), up-regulated the expression of PC by HGEC.…”
Section: Discussionsupporting
confidence: 54%
“…These results suggest that expression and/or activity of collagenolytic enzymes, in association with hyperglycaemia-induced modulation of integrin expression, may be at least partly responsible for Microvascular basement membranes in diabetes 539 GBM accumulation. Similar alterations were found in the expression of integrins in tubular epithelial cells, and in their interaction with basement membrane components [18].…”
Section: Glomerular Basement Membrane (Gbm)supporting
confidence: 60%
“…This activity was accompanied by increased metalloproteinase (MMP-2 and 9) production [54]. Proximal tubular cells cultured in the presence of high glucose concentration changed their pattern of integrin expression, as did glomerular epithelial [18] and mesangial cells [55]. It should be noted that in different renal cell types the changes in patterns of integrin expression are different.…”
Section: Tubular Basement Membranementioning
confidence: 99%
“…While not possessing kinase domains, integrin receptors can transduce information from the ECM to the cell to activate various intracellular signaling pathways, thereby regulating cellular processes as diverse as cytoskeletal organization, proliferation, differentiation, apoptosis, and cell migration (8,30,47,62,65). Numerous studies have linked integrins in the pathogenesis of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%